Contextual E-Comics in Geography: A Modern Pedagogical Tool for Volcanic Hazard Mitigation Awareness - Wijayanti, Friska Yuli; Handoyo, Budi; Dembereldorj, Uuriintuya (Future Space: Studies in Geo-Education, 2024)
Technological advancements have profoundly reshaped educational paradigms, leading to an expansive array of instructional media. Nevertheless, empirical observations reveal educators' hesitancy in assimilating these technologies, notably within geography instruction. Predominantly, geography pedagogy has gravitated towards memorization-based approaches, thereby constricting students' capacity to correlate academic content with their empirical experiences—a consequence of an entrenched reliance on conventional textbooks. Addressing this instructional void, our research endeavoured to devise an E-Comic media, underpinned by a contextual approach, to elucidate strategies for mitigating volcanic eruptions. The empirical setting for this study was situated at SMA PGRI 1 Lumajang. The research harnessed the Research and Development (R&D) methodology, employing the comprehensive ADDIE model. This model delineates five distinct phases: 1) Curricular, student demographic, and educator need analysis; 2) Storyboard conceptualisation for the impending product; 3) Product realisation in conformity with the established design; 4) Implementation, encompassing a rigorous vetting process by domain-specific expert validators and the intended research demographic. Evaluation metrics showcased robust approval ratings: 87% from media specialists, 97% from subject-matter experts, 95% from educator respondents, and 87% endorsement from student participants. In light of these affirmations, as conceptualised and developed in this study, the E-Comic medium is posited as an academically sound and pedagogically effective tool.